Uang Panggilan: Media Pertukaran Sosial dan Tolong Menolong dalam Masyarakat Gadih Angik - Zainal Abidin; Hulwati Hulwati (Indonesian Center for Religion and Society Studies (InTReSt), 2021)
This study raises the theme of Uang panggilan in the Gadih Angik Community Tradition. Call money is a form of tradition in the form of giving a kind of money to the host who is holding a baralek event. This tradition is carried out on the principle of mutual cooperation and mutual help, so of course if someone is invited and has paid the summons, then with a sincere heart, the person who was given the call money must also give when the person who gave earlier held a baralek event. So based on this, the question arises, how is the tradition of calling money in the baralek event in the tradition of the Gadih Angik community, starting from the formation factor, the implementation process and what are the implications of this tradition for the surrounding community. With a qualitative descriptive approach, this study will describe some of the data obtained from the field, both observational interviews and documentation as data collection methods. In addition, this research also uses a mix method, in the sense of a combination of social science research and Islamic law approach research, then also analyzed with 'urf and maqasyid shari'ah and with social exchange theory. From the factors that occur, the implementation process to the implications for society, it can be concluded that the law for the implementation of this tradition of calling money is permissible at the level of hajjiyah.